A Summary of the Precambrian Granitoid Rocks of the Kruger National Park - J.M. Barton (Koedoe: African Protected Area Conservation and Science, 1986)
Precambrian granitoid rocks underlie approximately 60 percent of the Kruger National Park. They occur primarily in the western portion of the park and comprise a wide variety of rock including granites, granodiorites, tonalites, trondhjemites and syenites spanning more than 1 500 Ma from the Archaean to the Proterozoic. Remnants of old greenstone belts are also found.